The extent of the use of modern educational models by teachers of philosophy and psychology and their impact on the level of concept acquisition - Hussein, Anas Ali; Alddine, Imad Seif (Journal of Tikrit University for Humanities, 2023)
This study aimed to reveal an analysis of the extent to which modern educational models are used by teachers of philosophy and psychology and its impact on the level of concept acquisition in the General Directorate of Education in Salah al-Din. The sample of the study consisted of teachers (31) male and female students, and their number reached (15) teachers and (16) schools, and the sample of students was (155) male and female students for the year 2022-2023 from the original community. On the extent to which modern educational models are used, it is in its final form of (20) paragraphs, and in front of each paragraph, three alternatives are placed (it applies to me a lot, it applies to me sometimes, it does not apply to me), and the second is the concept acquisition test, which in its final form consists of (30) paragraphs derived from (10) Concepts. The results of the study indicated the following: 1- The level of adoption of modern educational models by male and female teachers of philosophy and psychology is an average or acceptable level. 2- The level of adoption of modern educational models by teachers of philosophy and psychology is more than the level of adoption by teachers. 3- The level of the sample students in the concept acquisition test is high. 4- There are significant differences between male and female students and in favor of female students in the concept acquisition test. 5- modern educational models by male and female teachers of philosophy and psychology and the acquisition of psychological concepts and its fields among students.